TECNOLOGIA EDUCATIVA PARA VISITADORES DO PROGRAMA PRIMEIRA INFÂNCIA MELHOR - Holkmem, Giovania Aparecida de Lima (2021)
This Dissertation is part of the 2030 Agenda of the United Nations, more specifically, in the objectives: Health and Well-being (Improving maternal health and reducing neonatal mortality); it is also included in the National Agenda of Priorities in Health Research in Axis 4 - Development and Innovation of Health Technologies and Axis 14 - Maternal and Child Health, in addenda 14.6 and 14.7, which emphasize the analysis of the profile of access to health services , education and social assistance for children aged zero to five years, as well as in the development and/or evaluation of instruments for monitoring child development in Brazil, where the importance of research aimed at maternal and child health is reinforced. Based on local and regional demands, we sought to develop an innovative Educational Technology, consisting of a set of knowledge, applications and devices that allow the application of technological tools by visitors to Early Childhood Better when working with families, in the field of academic, professional and social education. The objective was, therefore, to identify the educational motivational strategies that facilitate and qualify the activities of the visitors of the Primeira Infância Melhor Program, in the municipality of Santa Maria/RS, and develop an Educational Technology, of the video/documentary type, based on experiences the being and doing of the visitors with the families assisted by the Better Early Childhood Program. The methodological path was conducted by a qualitative field study, with a descriptive, exploratory approach. The study population consisted of nine visitors who worked in the Program from 2014 to 2017, with data collection carried out from June to October 2020, with individual semi-structured interviews, answered via audio and in writing, with the participation of professionals from different backgrounds: social worker, psychologist, dentist, physiotherapist, occupational therapist and nurse. Based on the experiences lived by the visitors, four categories emerged as results, covering the potential, the professional's satisfaction and their experiences. Through the research, it was subsidized the construction of a documentary video with the accounts of the visitors' experiences and, also, the report of managers of the regional and state sphere. As for the discussions, the educational video is a motivational support for visitors who will be starting the Best Early Childhood Program, whose purpose is to motivate, qualify and train these professionals in their trajectory of visitation with their families. Through the generated product, a documentary video was created with four visitors who agreed to participate in the study, with the participation of two managers, one at the regional level and the other at the state level. The applicability of it and its relevance are due to the fact that the municipality does not have such technology and is configured as a motivational tool to support new visitors with the purpose of training and/or qualifying them for their professional performance, which may serve as a educational strategy for courses in the health area as a pedagogical tool.